In Situ Construction of Efficient Interface Layer with Lithiophilic Nanoseeds toward Dendrite‐Free and Low N/P Ratio Li Metal Batteries. Issue 8 (25th January 2022) - Luo, Lingli; Xia, Shuixin; Zhang, Xun; Yang, Junhe; Zheng, Shiyou
Abstract: Li metal is considered as one of the most promising candidates for constructing advanced high‐energy energy storage due to its ultrahigh theoretical capacity and lowest electrochemical potential. However, its practical commercialization is seriously hindered by the challenges of Li dendrite growth, low Coulombic efficiency, and huge volumetric variation. Herein, an efficient in situ generated Li2 S‐rich interface layer joint with preplanted Sb nano active sites in hosted Li metal anode is easily achieved with the nanosized Sb2 S3 decorated carbonaceous network. The yielded CC@Sb2 S3 @Li anode demonstrates uniform Li deposition, high Coulombic efficiency, and alleviated volumetric variation. Therefore, the Li symmetric cells show ultralong lifespan stable cycling over 3200 cycles with a very low voltage hysteresis (≈18 mV) at 5 mA cm −2 . Impressively, the Li|LiFePO4 full cell delivers an exceptionally prolonged cycling over 180 cycles with a superior capacity retention as high as ≈90% even under the harsh condition of an extremely low negative to positive capacity ratio of ≈0.44 with lean electrolyte (4.4 µL mAh −1 ). Moreover, the Li|LiNi0.5 Co0.2 Mn0.3 O2 full cell also maintains an excellent cycling performance under the more realistic harsh conditions. This work provides a new avenue and significant step paving the Li metal toward the practical application. Abstract : Sb2 S3 decorated carbonaceous 3D architecture is rationally exploited to stabilize Li metal. An efficient Li2 S‐rich interface layer and lithiophilic Sb nucleation sites are in situ constructed. The Li symmetric cells demonstrate an ultralong lifespan stable cycling and the full cells deliver extraordinarily prolonged cycling performance even under the harsh conditions of extremely low negative/positive capacity ratio and lean electrolyte.